2016
DOI: 10.1186/s13075-016-1194-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body weight on the achievement of minimal disease activity in patients with rheumatic diseases: a systematic review and meta-analysis

Abstract: BackgroundIn this study, we evaluated the impact of obesity and/or overweight on the achievement of minimal disease activity (MDA) in patients with psoriatic arthritis (PsA) and patients with rheumatoid arthritis (RA) receiving an anti-rheumatic treatment. Obesity can be considered a low-grade, chronic systemic inflammatory disease and some studies suggested that obese patients with rheumatic diseases exhibit a lower rate of low disease activity achievement during treatment with anti-rheumatic drugs.MethodsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 43 publications
2
33
1
3
Order By: Relevance
“…In summary, there is sufficient evidence demonstrating the high prevalence of comorbidity [2,4,5] in patients with PsA and its impact on outcome measures, treatment response and clinical decision-making [6,[9][10][11][12][13]. A number of studies have also highlighted that comorbidity clearly impairs function and quality of life in PsA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, there is sufficient evidence demonstrating the high prevalence of comorbidity [2,4,5] in patients with PsA and its impact on outcome measures, treatment response and clinical decision-making [6,[9][10][11][12][13]. A number of studies have also highlighted that comorbidity clearly impairs function and quality of life in PsA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the presence of comorbidities may influence the treatment response and decisionmaking process. Different studies have shown that both obesity and metabolic syndrome are associated with lower retention rates of and response rates to biological therapy [10][11][12], and a systematic literature review found that obesity and overweight reduce the odds to achieve minimal disease activity in patients with PsA receiving treatment with traditional or biologic drugs [13].…”
mentioning
confidence: 99%
“…In another meta-analysis of four previous studies, RA patients who were obese were 47% less likely to be in remission/low disease activity by DAS28 (OR 0.53, 95% CI 0.41, 0.69) (32). Most recently, in a meta-analysis of 10 prior studies, patients with obesity were 42% less likely to achieve minimal disease activity compared to patients with normal BMI (OR 0.58, 95% CI 0.40–0.85) (33). In a study performed in the Netherlands, continuous BMI was positively correlated with DAS28 ( r =0.34, p =0.001) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity negatively influences not only CVD risk but also other disease outcomes. In this regard, being obese and overweight reduces the chances to achieve minimal disease activity in patients with PsA receiving traditional or biologic DMARD therapy .…”
Section: Discussionmentioning
confidence: 99%